Teachers' Practices on Using CRA Approach in Teaching Grade Ten Mathematics - Bohara, Puskar Singh (AMC Journal (Dhangadhi), 2024)
The mathematical concept examines the connection between prior mathematical learning experiences and new information. Similarly, increased learner interest fosters a positive attitude toward mathematics. To improve teaching methods, teachers must understand current teacher practices. The CRA strategy includes three stages—concrete, representational, and abstract, to enhance conceptual learning and encourage active participation in teaching. In online journals, e-library (TU and KU), and Google scholars, I did not find any research study regarding practice of CRA approach in grade ten mathematics, especially in context of Nepal. So, this study aims to investigate how secondary mathematics teachers apply the CRA approach. The research question is: How do secondary-level mathematics teachers use concrete materials, representations, and abstract symbols in their instruction?The paper is based on qualitative research, involving interviews with five secondary mathematics teachers from different schools, each with at least five years of experience, and classroom observations to gather data on the use of the CRA pedagogical strategy. Data was collected through classroom observations, in-depth teacher interviews, and the author's personal teaching experiences. The interviews and other data were transcribed, categorized, themed, and analyzed to derive interpretations and findings (Saldana, 2016). It was discovered that most teachers implement the CRA approach in various ways, influenced by factors such as school environment, educational policy, curriculum content, student and parent characteristics, teacher abilities and experience, and available resources. Ultimately, for comprehensive learner development, teachers must be mindful of their pedagogy, content, and instructional materials to enhance learning in their subjects.